Inclusion and Resilience : The Way Forward for Social Safety Nets in MENA - Silva, Joana; Levin, Victoria; Morgandi, Matteo (World Bank, Washington, DC, 2013)
The Arab Spring and subsequent transitions provide opportunities for better governance, economies free of cronyism and more inclusive models of growth. Social Safety Nets (SSN) will be a key component of building more inclusive economies and societies. And here too there are grounds for optimism. Most SSN programs around the world were introduced during transition periods (post-Soviet independence, Indonesia's decentralization, and regime change in Brazil and Portugal), and have remained in place since. Effective SSNs can break the cycle of intergenerational poverty by helping families to keep children healthy and in school. SSNs and increased social services can also deal with spatial pockets of poverty in slums and rural areas by promoting the demand for social services and by building community assets. Most SSNs in the Middle East and North Africa (MENA SSNs) finance energy subsidies, crowding out more effective intervention. In addition to surveys, this study conducted a behavioral experiment among a representative sample of the Jordanian middle class, collecting information on preferences for redistribution to the poor using valuable trade-offs.